PENGARUH KEINGINTAHUAN DAN RASA PERCAYA DIRI SISWA TERHADAP HASIL BELAJAR MATEMATIKA KELAS VII MTs NEGERI I KOTA CIREBON - Irna Hanifah Ameliah; mumun munawaroh (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
In the world of education right now, a lot of complex issues occur and need special attention from all parties. One of them is the lack of curiosity and self-confidence of students thus affecting student learning results primarily on mathematical subjects. The better the curiosity and self-confidence of students, then students will be more motivated to learn. So the students will obtain a meaningful learning and get the results of the study are in accordance with the national education goals. The purpose of this research was to review; How big is the curiosity of students, how high the confidence of students, and how great the influence of curiosity and self-confidence of students toward outcome studied mathematics students. The research method used is the quantitative methods. The population in this research is grade VII MTs Negeri 1 CirebonÂ in the year 2014/2015 Lessons, with the number of students 1127 people. The technique of sampling using purporsive sampling. By using the selected sampling engineering 80 students to become respondents. The dwarf in the collection of data for the variable X is now with the spread against the target of research. As for the variable Y by using the test instrument. Then the data obtained were analyzed by using test normality, test its homogeneity, linierity test regression, autocorrelation test, and test the multikolinieritas as well as a test of the hypothesis. Based on the results of the analysis of the obtained an average score of curiosity is 59,25% by category and average score results of learning math is 69,11% with high category as well aÂ the average score of studen learning outcomes i.e. 67,81% by category enough. The result statistical hypothesis test note that 11,782>2,37 the Ho are received. With equation regresion is 83.866 + 0.128 0.364 x 1 + X 2 which means there are influences between curiosity and self-confidence of students toward outcome studied mathematics. Based on the determination of the magnitude of the influence coefficient is 4,79% meaning that curiosity and self-confidence of students gives only a small influence against the results of the study of mathematics students. While the rest of 95,21% is affected by other factors. Key words: students ' Curiosity, self-confidence of the students, the results of the study